Teologi Penciptaan sebagai Paradigma Epistemologis dalam Menanggapi Krisis Kebenaran Era Post-Truth - Santosa, Hansen; Antonius, Yosef; Mesakh, Jacob (Institut Agama Kristen Negeri Tarutung, 2025)
The post-truth era has challenged the epistemological foundations of Christians by making personal perspectives, individual feelings or emotions, even subjective opinions, and popular narratives the new standards of truth. This distorts the meaning of objective truth or biblical truth, which should be rooted in the Word of God. This article proposes creation theology as an alternative epistemological paradigm to address this crisis. By emphasising God as the Creator and Source of all truth, creation theology provides a solid ontological and epistemological foundation for understanding truth that is stable, integral, and transcendent. This approach is based on qualitative-descriptive methodology through a literature review of theological texts and the post-truth paradigm. It can be concluded that the characteristics and epistemological implications of the post-truth era highlight the crucial role of creation theology as a reference or ontological and epistemological foundation for truth. Christian epistemology from the perspective of creation theology serves as a critique of the relativism and subjectivism that have become prevalent within Christian communities. Therefore, there is a need for pastoral and educational implications for the church: to actualise the paradigm of creation theology.